Implementation of Human Resource Management Based on the Faith and Al-Qur'an Curriculum to Improve Teacher Competence in Kuttab Al Fatih Sidoarjo : Penerapan Manajemen Sumber Daya Manusia Berbasis Kurikulum Iman dan Al Qur’an untuk Meningkatkan Kompetensi Guru di Kuttab Al Fatih Sidoarjo - Choirunisa Karina; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Human resource management in Islamic educational institutions plays a central role in shaping teacher professionalism and sustaining character-based education. Specific Background: Kuttab Al-Fatih Sidoarjo implements a curriculum based on Iman and Al-Qur’an, requiring systematic management to support teacher competence, particularly pedagogical competence. Knowledge Gap: Previous studies have discussed human resource management in Islamic schools, yet limited research specifically analyzes POAC-based management integrated with an Iman and Al-Qur’an curriculum in the context of Kuttab institutions. Aims: This study aims to analyze the implementation of human resource management based on the Iman and Al-Qur’an curriculum using the POAC framework to develop teacher pedagogical competence at Kuttab Al-Fatih Sidoarjo. Results: Findings indicate that structured recruitment through Akademi I’dad Mudarrisin, organized role distribution, routine professional development programs, and continuous evaluation contribute to systematic teacher development, although time management constraints remain. Novelty: The study presents an integrated POAC-based human resource management model grounded in a dual curriculum of Iman and Al-Qur’an within a Kuttab educational setting. Implications: The model provides a reference for Islamic educational institutions seeking structured teacher development aligned with faith-based curriculum management. Keywords: Human Resource Management, Iman and Al-Qur’an Curriculum, POAC, Teacher Competence, Kuttab Education Key Findings Highlights: Structured recruitment through a dedicated teacher academy supports systematic staff preparation. Continuous mentoring programs sustain professional growth within daily institutional routines. Regular evaluation mechanisms identify operational constraints related to scheduling and coordination.